2002
DOI: 10.1139/g02-038
|View full text |Cite
|
Sign up to set email alerts
|

Measuring conservation of contiguous sets of autosomal markers on bovine and porcine genomes in relation to the map of the human genome

Abstract: Based on published information, we have identified 991 genes and gene-family clusters for cattle and 764 for pigs that have orthologues in the human genome. The relative linear locations of these genes on human sequence maps were used as "rulers" to annotate bovine and porcine genomes based on a CSAM (contiguous sets of autosomal markers) approach. A CSAM is an uninterrupted set of markers in one genome (primary genome; the human genome in this study) that is syntenic in the other genome (secondary genome; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Comparative genomics can be used to investigate complex multigenic biological phenomenon, as in principle, essential mechanisms should be conserved in relatively closely related species. Cattle and humans share 72% sequence homology [1] and higher sequence similarity, on average, than that exhibited between human and mouse (F. S. L. Brinkman, unpublished data). Mouse is often used as the animal model of choice to study infectious diseases and the resulting immune responses in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomics can be used to investigate complex multigenic biological phenomenon, as in principle, essential mechanisms should be conserved in relatively closely related species. Cattle and humans share 72% sequence homology [1] and higher sequence similarity, on average, than that exhibited between human and mouse (F. S. L. Brinkman, unpublished data). Mouse is often used as the animal model of choice to study infectious diseases and the resulting immune responses in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…An inversion of gene order was defined between 80 and 150 Mb of human chromosome 4 (GPIG4 to EDNRA) which corresponds from 70 cM to the end of the linkage group on pig chromosome 8, consistent with previous reports. 1 This breakpoint likely lies between SCARB2 and GPIG4 at 78 and 82 Mb, respectively.…”
mentioning
confidence: 98%
“…Source/description: The potassium inwardly rectifying channel, subfamily J, member 8 gene (KCNJ8), previously termed KIR6.1, maps to HSA 12p11.23 and encodes an integral membrane protein and inward-rectifier type potassium channel. 1 The human gene consists of three exons spanning about 9.7 kb and the encoded protein, which has a greater tendency to allow potassium to flow into a cell rather than out of a cell, is controlled by G-proteins. 1 KCNJ8 is expressed preferentially in human heart muscle.…”
mentioning
confidence: 99%
“…It has been shown (Jiang et al, 2002) that several genes found in the region from 16.2 to 32.2 Mb on human chromosome 1 are located in region of conserved synteny on bovine chromosome 2. The RH 5,000 map (Band et al, 2000) located six genes from this HSA1 region on BTA2.…”
Section: Discussionmentioning
confidence: 99%